Shifting Positions: Party Positions and Political Manifestos in Costa Rica. (22nd February 2023) - Chavarría-Mora, Elías; Angell, Katie
ABSTRACT: This article analyzes how niche parties may utilize a strategy of policy shifting to garner additional voters. It leverages a unique opportunity in which a Costa Rican political party released two different versions of its party manifesto at different moments during a single election cycle. This rare opportunity uncovers how the party shifted from having a hard conservative stance on social issues, such as abortion, to moderating its stance and centering its focus on less contentious issues in a runoff election campaign. Understanding how a single political party may alter its strategy is important because it allows us to better gauge the effectiveness of shifting policy positions, especially for niche parties, for which a particular issue area is dominant. Moreover, this analysis opens additional avenues of research on political parties in the Latin American context, since research utilizing manifesto data in this context has been limited.